What is the American business value system? - De George, Richard T. (Journal of business ethics, 1982)
The model of free enterprise that has developed in the United States presupposes a value system. The central value is freedom. Next come goods and the means of acquiring them, viz., money and profit. Competition is central. But fairness of transactions is presupposed, and this implies honesty, truthfulness, and general respect for persons. Optimism and faith in the future have been ingredients from the start. Each of these values can be abused, and such abuses characterize the seamy side of capitalism. The Myth of Amoral Business helps undermine the values. Yet the changes American society is demanding of business can be seen as reaffirming the values the system presupposes. The imperative is for business to live up to its own best traditions — a social demand that business can and should meet if it wishes to continue as a system of free enterprise.